PENGARUH METODE KARYAWISATA TERHADAP HASIL BELAJAR MENULIS TEKS PUISI - Usman Usman; Sakaria Sakaria; Hasriawanda Ummy Haris (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2023)
The Effect of the Field Trip Method on Students' Poetry Text Writing Learning Outcomes. This study aims to determine the effect of the field trip method on the learning outcomes of writing poetry texts for class VII students of SMPN 1 Turikale Maros. This research is an experiment with a sample of 32 students. Data collection techniques used by researchers in the form of tests in the form of pretests and posttests The collected data is then processed and analyzed using inferential statistical analysis and descriptive statistics. The research results show that the use of the field trip method has an effect on learning to write poetry texts. The field trip method can provide a stimulus for students to express ideas and ideas in writing poetry based on objects that are felt, seen, and heard.